2017
DOI: 10.4103/aca.aca_25_17
|View full text |Cite
|
Sign up to set email alerts
|

The utility of preoperative level of erythrocytosis in the prediction of postoperative blood loss and 30-day mortality in patients with tetralogy of fallot

Abstract: Background:Postoperative major bleeding is a relatively common complication of patients undergoing corrective surgery of tetralogy of Fallot (TOF). Life-threatening blood losses can lead to aggressive transfusions or reoperation. Little is known about the risk factors associated with a bleeding tendency in TOF patients. This study aimed to establish predictive models for postoperative blood loss and mortality in TOF patients.Methods:We conducted a retrospective observational study involving patients with TOF w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Machine learning was the most represented with 38 included studies describing its use, 13 23 28 29 31 32 , 34 , 35 , 36 , 38 , 39 , 40 , 42 44 46 47 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 70 whereas two applications incorporated the use of fuzzy logic 21 , 22 and only one study described the use of each of natural language processing 23 and computer vision. 13 Many branches of machine learning were discussed, including regression models, 29 45 46 49 50 51 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 decision trees, 23 , 33 , 34 , 35 expert systems, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning was the most represented with 38 included studies describing its use, 13 23 28 29 31 32 , 34 , 35 , 36 , 38 , 39 , 40 , 42 44 46 47 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 70 whereas two applications incorporated the use of fuzzy logic 21 , 22 and only one study described the use of each of natural language processing 23 and computer vision. 13 Many branches of machine learning were discussed, including regression models, 29 45 46 49 50 51 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 decision trees, 23 , 33 , 34 , 35 expert systems, …”
Section: Resultsmentioning
confidence: 99%
“… 13 Many branches of machine learning were discussed, including regression models, 29 45 46 49 50 51 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 decision trees, 23 , 33 , 34 , 35 expert systems, 59 K-means classifiers, 35 K-nearest neighbours, 29 , 44 Bayesian approaches, 29 neural networks, 23 , 25 , 34 , 45 random forest models, 23 29 31 , 45 , 46 , 47 and support vector machines. 34 , 45 , 70 Regression models were the most commonly described, with one study describing a linear regression model, 50 23 studies describing logistic regression models, 29 36 46 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the percentage of HCT before surgery in cases with death outcome was higher than those survived (0.047). In a same way, Guevara et al showed that preoperative haematocrit showed statistically significant association with 30-day mortality [ 33 ]. Actually haematocrit increases in TOF patients as a response to hypoxia [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guevara et al [26] developed a predictive model for 30-day mortality in children undergoing corrective surgery of tetralogy of Fallot. Additionally, the authors found that preoperative hematocrit and duration of intraoperative oxygenator with cardiopulmonary bypass were significantly correlated with postoperative blood loss within 24 h postop [26].…”
Section: Models To Predict Adverse Events For Specific Patient Popula...mentioning
confidence: 99%